Starting maternal exercise, unlike reducing the intensity of exercise during pregnancy, prevents memory deficits in female offspring subject to maternal deprivation - Carrazoni, Guilherme Salgado; das Neves, Ben-Hur Souto; dos Santos Soares, Marisele; Lima, Karine Ramires; Mello-Carpes, Pâmela B. (Brain research, 2023)
[Display omitted] •Running at pregnancy prevents maternal deprivation (MD) memory deficits in female offspring.•Running before and reducing the intensity during pregnancy does not prevent MD-induced deficits.•Running protects against MD-induced oxidative damage in MD female offspring.•Running improves antioxidant capacity in MD female offspring. Maternal deprivation (MD) leads to long-lasting memory deficits. Conversely, maternal exercise could potently modify the offspring's cellular machinery. Here, we tested whether starting to run or reducing the intensity of running during pregnancy can protect prepubertal female offspring against MD-induced memory deficits. Female rats were divided into different groups submitted or not to MD: one started to run before pregnancy and reduced the intensity during the pregnancy (PGE); another started to run at the beginning of pregnancy (GE); and, finally, a control group (CT) was not submitted to exercise. All the rats but those of the CT ran on a treadmill until the delivery day (PND 0). Subsequently, MD was performed from PND 1 to 10. We assessed object recognition (OR) and spatial memory (SM) of female offspring after weaning (PND22, pre-pubertal stage). MD caused OR memory deficit; GE female offspring did not present this deficit, but PGE did. Both PGE and GE alone enhanced offspring spatial learning, but their combination with MD impaired it. MD promoted hippocampal lipid peroxidation increase, which both PGE and GE prevented. Total antioxidant capacity in the hippocampus was higher in both MD-exercised groups compared to all others. Although the antioxidant effects of exercise were similar in both MD exercise groups, we observed better results in the memory tests in the GE group than in the PGE group. These results suggest that starting to exercise during pregnancy is better than reducing the exercise intensity during pregnancy to prevent MD-induced memory deficits in female offspring.